Answer: ![15r^2-21r+5](https://tex.z-dn.net/?f=15r%5E2-21r%2B5)
Step-by-step explanation:
Given: Perimeter of triangular garden = ![25r^2 - 9r + 14](https://tex.z-dn.net/?f=25r%5E2%20-%209r%20%2B%2014)
The sum of two sides of the garden = ![10r^2 + 12r + 9](https://tex.z-dn.net/?f=10r%5E2%20%2B%2012r%20%2B%209)
Perimeter is the sum of all sides of a triangle.
Third side = Perimeter of triangular garden - sum of two sides of the garden
![=25r ^ 2 - 9r + 14-(10r ^ 2 + 12r + 9)\\\\=25r ^ 2 - 9r + 14-10r ^ 2 - 12r - 9\\\\=15r^2-21r+5](https://tex.z-dn.net/?f=%3D25r%20%5E%202%20-%209r%20%2B%2014-%2810r%20%5E%202%20%2B%2012r%20%2B%209%29%5C%5C%5C%5C%3D25r%20%5E%202%20-%209r%20%2B%2014-10r%20%5E%202%20-%2012r%20-%209%5C%5C%5C%5C%3D15r%5E2-21r%2B5)
The expression represent the third side =
.
Answer:
(3x+1)(x+3) is the factorised form for the expression.
Step-by-step explanation:
:3
x
2
+
10
x
+
3
We can Split the Middle Term of this expression to factorise it.
In this technique, if we have to factorise an expression like
a
x
2
+
b
x
+
c
, we need to think of 2 numbers such that:
N
1
⋅
N
2
=
a
⋅
c
=
3
⋅
3
=
9
and,
N
1
+
N
2
=
b
=
10
After trying out a few numbers we get:
N
1
=
9
and
N
2
=
1
9
⋅
1
=
9
, and
9
+
(
1
)
=
10
3
x
2
+
10
x
+
3
=
3
x
2
+
9
x
+
1
x
+
3
=
3
x
(
x
+
3
)
+
1
(
x
+
3
)
(
3
x
+
1
)
(
x
+
3
)
is the factorised form for the expression.
is the factorised form for the expression.
Add 1 to both sides:
![\sqrt{x+3} = x+1](https://tex.z-dn.net/?f=%20%5Csqrt%7Bx%2B3%7D%20%3D%20x%2B1%20)
In cases like this, we have to remember that a root is always positive, so we can square both sides only assuming that
![x+1 \geq 0 \iff x \geq -1](https://tex.z-dn.net/?f=%20x%2B1%20%5Cgeq%200%20%5Ciff%20x%20%5Cgeq%20-1%20)
Under this assumption, we square both sides and we have
![x+3 = (x+1)^2 \iff x+3 = x^2+2x+1 \iff x^2+x-2 = 0](https://tex.z-dn.net/?f=%20x%2B3%20%3D%20%28x%2B1%29%5E2%20%5Ciff%20x%2B3%20%3D%20x%5E2%2B2x%2B1%20%5Ciff%20x%5E2%2Bx-2%20%3D%200%20)
The solutions to this equation are
![x = -2,\ x=1](https://tex.z-dn.net/?f=%20x%20%3D%20-2%2C%5C%20x%3D1%20)
But since we can only accept solutions greater than -1, we discard
and accept
.
In fact, we have
![x=-2 \implies \sqrt{-2+3}-1=0\neq -2](https://tex.z-dn.net/?f=%20x%3D-2%20%5Cimplies%20%5Csqrt%7B-2%2B3%7D-1%3D0%5Cneq%20-2%20)
and
![x=1 \implies \sqrt{4}-1=1](https://tex.z-dn.net/?f=%20x%3D1%20%5Cimplies%20%5Csqrt%7B4%7D-1%3D1%20)
which is the only solution.
Answer: C & D
Step-by-step explanation: